AYURVEDA REVIEW ON â€œDADIMASHTAKA CHURNAâ€ AND ITS CLINICAL IMPORTANCE - Narang, Ranjit; Herswani, Isha (Journal of Drug Delivery and Therapeutics, 2018)
Dadimashtaka Churna a polyherbal Ayurvedic formulation mainly used for gastro intestinal problem such as; diarrhea. Tawaksheeri, Twak, Patra, Ajamoda, Dhanyaka, Ajaji, Granthi, Pippali, Dadima and Sita are the main ingredients of formulation. Dadimashtaka churna prepared by mixing various herbs with sugar and traditionally it is recommended to take 3 to 5 grams of formulation with warm water/rice soup after meal. However it should be used cautionary with diabetic patients. The presence of various chemical constituents of different herbs makes this formulation worth full for gastric trouble especially digestive problems. The folklore use of Dadimashtaka churna needed to explore to enhance global acceptance of this formulation, considering this fact current article summarizes various aspect of Dadimashtaka churna. Keywords: Ayurveda, Dadimashtaka Churna, Sita and Diarrhea.